Boswellia serrata in osteoarthritis and rheumatoid arthritis: effects, mechanisms, and clinical evidence - Koszewski, Jakub Kazimierz; Pielak, Wiktoria; Janiszewska, Anna; Kołkowski, Wiktor; Jakubczyk, Jan; Wądołowska, Monika; Antoszewska, Magdalena; Grabowska, Maria; Gozdera, Katarzyna; Oszast, Katarzyna (Quality in Sport, 2026)
Background. Osteoarthritis (OA) and rheumatoid arthritis (RA) carry a large global burden, and standard pharmacotherapy is limited by gastrointestinal, renal and cardiovascular toxicity. Boswellia serrata oleogum resin has re-emerged as an anti-inflammatory adjunct. Aim. To summarise current evidence on the phytochemistry, mechanisms, pharmacokinetics, clinical efficacy, and safety of Boswellia serrata in OA and RA. Materials and methods. A structured search of PubMed, bioRxiv, Scopus and Google Scholar (1990–2026, with seminal pre-1990 records retained) combined Boswellia serrata, boswellic acid, AKBA, 5-LOX, NF-B, osteoarthritis, rheumatoid arthritis, pharmacokinetics and clinical trial. Results. Boswellic acids, primarily AKBA, act through allosteric 5-LOX inhibition, IKK–NF-B suppression, anti-cytokine and anti-MMP effects, cathepsin G inhibition and Nrf2/HO-1 antioxidant activity. Standardised extracts produce clinically meaningful reductions in WOMAC and VAS scores in knee OA, and a Cochrane synthesis reports a 17-point VAS reduction at 90 days (NNT 2). RA evidence is sparser and provisional. Short-term safety is favourable; rare hepatic signals and CYP3A4-mediated interactions warrant attention. Conclusions. Boswellia serrata is a multi-target adjunct with a reproducible mechanism, consistent symptomatic benefit in OA, an evidence-light role in RA and acceptable short-term safety; manufacturer-independent multi-centre RCTs are the priority.